Potensi Akulturasi Budaya dalam Menunjang Kunjungan Wisatawan di Kota Semarang - Septemuryantoro, Syaiful Ade (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2020)
Abstract: Semarang as a multicultural city which there is a mixture of three ethnics groups, namely Javanese ethnics, Arab ethnics and Chinese ethnics. Semarang has a cultural acculturation that comes from three etnics. SemarangÂ has a special food called â€œLunpiaâ€. Semarang has a variety of festivalâ€™s such as the Chinese New Year, Cheng Ho Festival, Dugderan Festival. One example : Dugderan festival is held welcoming ramadhan. Warag ngendog is a mythological animal with carrying eggs on its back, this creature celebrated during the dugderan festival held annualy a few days before the Ramadhan. Represent three different etnics groups in Semarang city is a Javanese ethnics, Arabian ethnics, and Chinese ethnics. Its head is like a dragon, the body is the combination of Â camel and the legs is teh combination of goat. Gambang Semarang is one of traditional dance in Semarang. Gambang Semarang dance is showed to be enjoyed from its moving, appearance and rhythm and the dance is a reflection of someone action which enjoy their life, joyful and thankfull to God (Allah SWT), because we have been given grace through beautiful dance. Gambang Semarang dance using gamelan instrument including Kendang, kempul, bonang, gong, kecrek and tohyan (chinese). Song in Gambang Semarang dance exhivition feels happy and fresh, in January 2020 tourist arrivals in Semarang decreased until 6 percen, because in Jauary is not a period holiday (low season period). Ahmad Yani International Airport in Semarang i sthe entrance point for foreign. In January 2020, Malaysia were the highest number of tourist in Semarang (849people), Singapore (279 people) and Chinese (113 people). Keywords:Â cultural, acculturation, food, festival